2019
DOI: 10.1038/s41467-019-11270-1
|View full text |Cite
|
Sign up to set email alerts
|

Adipose group 1 innate lymphoid cells promote adipose tissue fibrosis and diabetes in obesity

Abstract: Pathogenic factors driving obesity to type 2 diabetes (T2D) are not fully understood. Group 1 innate lymphoid cells (ILC1s) are effectors of innate immunity and enriched in inflamed tissues. Here we show that the number of adipose ILC1s increases in obese T2D patients and correlates with glycemic parameters and with the number of ILC1s in the blood; circulating ILC1 numbers decrease as a result of metabolic improvements after bariatric surgery. In vitro co-culture experiments show that human adipose ILC1s prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 34 publications
1
65
0
1
Order By: Relevance
“…Higher numbers of circulating and adipose ILC1-like cells expressing IFN-γ have also been detected in obese subjects. Numbers of adipose ILC1-like cells are further increased in obese subjects with type 2 diabetes and correlate with insulin resistance [107]. A caveat with this hypothesis is that the genetic ablation tools to definitively differentiate between the contribution of each subset of group 1 ILCs to obesity-associated insulin resistance do not currently exist, and current flow cytometry-based strategies to identify human ILC1s are not specific [9].…”
Section: Ilc Activation Disrupts Metabolic Homeostasis During Diet-inmentioning
confidence: 99%
“…Higher numbers of circulating and adipose ILC1-like cells expressing IFN-γ have also been detected in obese subjects. Numbers of adipose ILC1-like cells are further increased in obese subjects with type 2 diabetes and correlate with insulin resistance [107]. A caveat with this hypothesis is that the genetic ablation tools to definitively differentiate between the contribution of each subset of group 1 ILCs to obesity-associated insulin resistance do not currently exist, and current flow cytometry-based strategies to identify human ILC1s are not specific [9].…”
Section: Ilc Activation Disrupts Metabolic Homeostasis During Diet-inmentioning
confidence: 99%
“…In T2DM, the numbers of circulating as well as adipose tissue-resident ILC1s are increased compared with normal individuals (184,185). The frequency of circulating ILC1s is positively correlated with fasting plasma glucose (FPG), HbA1c, homeostasis model assessment for insulin resistance (HOMA-IR), serum-free fatty acids (FFAs) and adipose tissue insulin resistance index (Adipo-IR) (184,185). It has also been shown that patients with increased numbers of ILC1 have an elevated risk of developing T2DM (184).…”
Section: Innate Lymphoid Cells (Ilcs)mentioning
confidence: 99%
“…Moreover, obesity could drive the secretion of IL-15 by adipose tissue macrophages, which has been demonstrated to have a positive effect on NK cell metabolism, proliferation and activation ( 84 ). In addition to NK cells, it is recently found that IL-12 activation of ILC1s is also implicated in driving obesity-associated adipose tissue inflammation ( 85 , 86 ). In summary, these studies suggest that obesity leads to the overaction of adipose NK cells, but loss of function of peripheral NK cells, which further contributes to obesity-related pathology and attenuated immunosurveillance, respectively.…”
Section: Nk Cell Metabolism In Diseasementioning
confidence: 99%